The effect of perceived value dimensions on customer loyalty with the mediation of customer loyalty with the mediation of customer satisfaction attributes - Wu, Fan (Tanjong Malim, 2024)
The effect of perceived value dimensions on customer loyalty with the mediation of customer loyalty with the mediation of customer satisfaction attributes by Wu, Fan